Greater Food Reward Sensitivity Is Associated with More Frequent Intake of Discretionary Foods in a Nationally Representative Sample of Young Adults - Nansel, Tonja R.; Lipsky, Leah M.; Eisenberg, Miriam H.; Haynie, Denise L.; Liu, Danping; Simons-Morton, Bruce (Frontiers in Nutrition, 2016)
Food reward sensitivity may influence individual susceptibility to an environment replete with highly palatable foods of minimal nutritional value. These foods contain combinations of added sugar, fat, and/or salt that may enhance their motivational salience. This study examined associations of food reward sensitivity with eating behaviors in the NEXT Generation Health Study, a nationally representative sample of US young adults. Participants (n=2202) completed self-report measures including the Power of Food Scale, assessing food reward sensitivity, and intake frequency of 14 food groups. Multiple linear regressions estimated associations of food reward sensitivity with each of the eating behaviors adjusting for covariates. Higher food reward sensitivity was associated with more frequent intake of fast food (b±linearized SE=0.24±0.05,p<.001), sweet and salty snacks (0.21±0.05,p<0.001), foods made with cheese (0.14±0.06,p=0.03), soda (0.12±0.04,p=0.009), processed meats (0.12±0.05,p=0.045), and fish (0.08±0.03 p=0.03), but was not associated with intake frequency of fruit or juice, green or orange vegetables, beans, whole grains, nuts/seeds, or dairy products. Food reward sensitivity was associated with greater intake of discretionary foods, but was not associated with intake of most health-promoting foods, suggesting food reward sensitivity may lead to preferential intake of unhealthful foods.